Diffracting digital images
1 online resource
Keywords: "Digital imaging techniques have been rapidly adopted within archaeology and cultural heritage practice for the accurate documentation of cultural artefacts. But what is a digital image, and how does it relate to digital photography? The authors of this book take a critical look at the practice and techniques of digital imaging from the stance of digital archaeologists, cultural heritage practitioners and digital artists. Borrowing from the feminist scholar Karen Barad, the authors ask what happens when we diffract the formal techniques of archaeological digital imaging through a different set of disciplinary concerns and practices. Diffracting exposes the differences between archaeologists, heritage practitioners and artists and foregrounds how their differing practices and approaches enrich and inform each other. How might the digital imaging techniques used by archaeologists be adopted by digital artists, and what are the potentials associated with this adoption? Under the gaze of fine artists, what happens to the fidelity of the digital images made by archaeologists, and what new questions do we ask of the digital image? How can the critical approaches and practices of fine artists inform the future practice of digital imaging in archaeology and cultural heritage? Diffracting Digital Images will be of interest to students and scholars in archaeology, cultural heritage studies, anthropology, fine art, digital humanities, and media theory"--